Bauhaus / 154 llustrations - 16 in Color - Thames And Hudson; Whitford Frank (1984)
Setting everything firmly against a backdrop of the times, Frank Whitford traces the ideas behind its conception and describes its teaching methods. Preface, Aims and Ambitions, Arts and Crafts and Architecture and the Academies, Art Education Reformed, The Founder, Problems, The First Appointments, The Students, Achievements, New Arrivals, The Basic Course: Color and Form, Going Dutch, Towards a New Unity: Moholy-Nagy and Albers, The Public Face, Dessau, Young Masters, A New Director, The Bitter End, Judgements, Documents, Bibliography, Sources of Quotations, Index.